Application of Kahoot Media to Improve Student Learning Outcomes in Finding Vocabulary and Meaning of Vocabulary Relating to Social Life - Dwi Susanti (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve student learning outcomes in finding vocabulary and vocabulary meanings related to social life. This research is a classroom action research (PTK) which is carried out in three cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were students of class II SD Negeri Sukareja 02 in the 2020/2021 school year, totaling 14 students. Data collection techniques using tests. Data analysis includes data reduction, data presentation, and drawing conclusions. Research shows that the application of Kahoot media can improve student learning outcomes in the material of finding vocabulary and meaning related to social life in class II SD Negeri Sukareja 02 in the academic year 2020/2021 as evidenced by the percentage of completeness of learning outcomes in cycle I of 71%, cycle II of 86 %, and becomes 93% in cycle III.